O-007 First US multicenter experience using the pipeline flex embolization device with shield technology for treatment of intracranial aneurysms – periprocedural outcomes and early safety profile. (23rd July 2022) - Kuhn, A; Singh, J; Abdelsalam, A; Saini, V; Burks, J; Cortez, G; Abbas, R; Pervez, M; Saei, H; Burke, S; Naragum, V; Massari, F; et al.
Abstract : Introduction/Purpose: Since becoming available in 2007, flow diverters introduced the principle of endovascular reconstruction of the parent artery and exclusion of the aneurysm from the blood circulation, which has revolutionized intracranial aneurysm treatment. Despite the overall positive results, a major concern of flow diverter implantation is possible ischemic and thromboembolic complications. To reduce material thrombogenicity, the PED Flex device underwent surface modification with covalently bonded phosphorylcholine to the surface of the implant, so called Shield Technology™. This technology has been shown to reduce thrombogenicity and promote endothelialization with earlier and thicker neointima formation but less hyperplasia. Materials and Methods: Prospectively maintained neurointerventional databases at 7 high-volume U.S. medical centers were retrospectively reviewed between April 2021 (corresponding with the FDA approval of the PED Shield) and October 2021. Additionally, compassionate use cases between 2016 and 2020 were also included. All patients who underwent placement of a PED Shield for treatment of a ruptured or unruptured intracranial aneurysm were identified. Patients who underwent re-treatment of an intracranial aneurysm due to failed primary treatment method were also included. Patient demographics, information on aneurysm size, morphology, and location as well as procedural data including device(s) used, adjunctive coiling and/or balloon angioplasty performed, intraprocedural complications, patient early angiographic and clinical outcome was collected. Results: One hundred thirty-eight patients were included (111 women) with 147 aneurysms. Eight aneurysms were ruptured. The patient's mean age was 58 years. Most aneurysms were located along the ICA (n=120), specifically along the ophthalmic segment (n=55), wide-necked (n=121) and saccular in shape (n=110). Mean aneurysm size was 4.3 mm (1.5 – 22 mm). PED Shield deployment was technically successful in 136 cases (98.6%). Balloon angioplasty was performed in 22 cases (15.9%). Aneurysm stasis after device deployment was seen in 86 aneurysms (58.5%). No major ischemic stroke or neurological death occurred. Transient ischemic attack was seen in 2 patients (1.4%). One patient suffered an intraparenchymal bleed on post-op day 11 and 1 patient had a minor stroke leading to overall permanent neurological morbidity of 1.4%. Conclusion: Our study is the first to report the early experience with the newly FDA-approved PED Flex with Shield technology amongst US centers. Our results are comparable with non-US, international studies showing a high technical success rate and safe peri-procedural angiographic and patient outcome. Long-term follow-up will be needed to provide more robust data on angiographic and patient outcomes. Disclosures: A. Kuhn: None. J. Singh: None. A. Abdelsalam: None. V. Saini: None. J. Burks: None. G. Cortez: None. R. Abbas: None. M. Pervez: None. H. Saei: None. S. Burke: None. V. Naragum: None. F. Massari: None. S. Marwah: None. M. Gounis: 1; C; National Institutes of Health (NIH), the United States – Israel Binational Science Foundation, Anaconda, ApicBio, Arsenal Medical, Axovant, Balt, Cerenovus, Ceretrieve, CereVasc LLC, Cook Medical, Gal. 2; C; Alembic LLC, Astrocyte Pharmaceuticals, BendIt Technologies, Cerenovus, Imperative Care, Jacob's Institute, Medtronic Neurovascular, Mivi Neurosciences, phenox GMbH, Q'Apel, Route 92 Medical, Stryker. 4; C; Imperative Care, InNeuroCo, Galaxy Therapeutics and Neurogami. A. Hassan: 1; C; GE Healthcare and Valley Baptist. 2; C; Medtronic, Microvention, Stryker, Penumbra, Cerenovus, Genentech, GE Healthcare, Scientia, Balt, Viz.ai, Insera therapeutics, Proximie, NeuroVasc, NovaSignal, Vesalio, Rapid Medical, Imperative Care a. A. Malek: 2; C; CereVasc Inc. 4; C; CereVasc Inc. G. Dabus: 2; C; Medtronic, Microvention, Cerenovus, Penumbra, Stryker, InNeuroCo, Route 92. I. Linfante: 2; C; Medtronic, Stryker, Cerenovus. 4; C; InNeuroCo, Deinde, Prometeous, Three Rivers, Prolong Pharmaceuticals. S. Tjoumakaris: 2; C; Medtronic and Microvention (funds paid to institution, not personally). P. Jabbour: 2; C; Medtronic, Microvention and Cerus. R. Hanel: 1; C; NIH, Interline Endowment, Microvention, Stryker and CNX. 2; C; Medtronic, Balt, Stryker, Q'Apel medical, Codman Neuro (J&J), Cerenovus, Microvention, Imperative Care, Phenox and Rapid Medical. R. Starke: 1; C; NREF, Joe Niekro Foundation, Brain Aneurysm Foundation, Bee Foundation, and by National Institute of Health (R01NS111119-01A1) and (UL1TR002736, KL2TR002737) through the Miami Clinical and Translation, unrestricted research grant from Medtronic. 2; C; Penumbra, Abbott, Medtronic, Balt, InNeuroCo, Cerenovus, Naglreiter and Optimize Vascular. A. Puri: 1; C; NIH, Microvention, Cerenovus, Medtronic Neurovascular and Stryker Neurovascular. 2; C; Medtronic Neurovascular, Stryker NeurovascularBalt, Q'Apel Medical, Cerenovus, Microvention, Imperative Care, Agile, Merit, CereVasc and Arsenal Medical. 4; C; InNeuroCo, Agile, Perfuze, Galaxy and NTI.